IMMEDIATE PAIN RELIEF BY MICROVASCULAR DECOMPRESSION FOR IDIOPATHIC TRIGEMINAL NEURALGIA - Haq, Naeem ul; Ali, Mumtaz; Khan, Hayat Mohammad; Ishaq, Muhammad; Khattaq, Muhammad Ishfaq (Journal of Ayub Medical College Abbottabad, 2016)
Background: Trigeminal neuralgia is a common entity which is managed by neurosurgeons in day to day practice. Up-till now many treatment options have been adopted for it but micro-vascular decompression is much impressive in terms of pain control and recurrence rate in all of them. The objective of study was known the efficacy of micro vascular decompression for idiopathic trigeminal neuralgia by using muscle patch in terms of immediate pain relief. Methods: This descriptive study was carried out in Neurosurgery Department lady reading hospital, Peshawar from January 2010 to December 2012. All patients who underwent micro vascular decompression for idiopathic trigeminal neuralgia were included in the study. Patients were assessed 72 hours after the surgery by borrow neurological institute pain scale (BNIP scale) for pain relief and findings were documented on predesigned pro forma. Data was analysed by SPSS-17. Results: Total 52 patients were included in this study. Among these 32 (61.53%) were female and 20 (38.46%) were males having age from 22-76 years (mean 49 years). Right side was involved in 36 (69.23%) and left side in 16 (30.76%) patients. Duration of symptoms ranged from 6 months to 16 years (mean 8 years). History of dental extraction and peripheral neurectomy was present in 20 (38%) and 3(5.76%) patients while V3 was most commonly involved branch with 28(57.69%) frequency and combined V2,V3 involvement was 1 (11.53%). Superior cerebellar artery was most common offending vessel in 46(88.46%) while arachnoid adhesions were in 2(3.84%) patients. We assessed patient’s immediate postoperatively using BNIP pain scale. Conclusion: Micro-vascular decompression is most effective mode of treatment for trigeminal neuralgia in terms of immediate pain relief.